Experimental and numerical investigation of suddenly expanded flow field for supersonic Mach numbers with and without annular cavities - Quadros, Jaimon Dennis; Khan, Sher Afghan; Prashanth, T. (Begell House, Inc., 2020)
The influence of cavities on a suddenly expanded flow field was analyzed. Air flow was passed through a convergent divergent axisymmetric nozzle, and expanded suddenly into a circular parallel shroud with annular cavities. Base pressure and wall pressures were measured for combinations of process variables, such as Mach number (M), nozzle pressure ratio (NPR), area ratio (AR), the length to diameter ratio (L/D) of the enlargement section, and the cavity aspect ratio. The experimental results showed that the base pressure fin the suddenly expanded flow field was significantly influenced by annular cavities for low area ratios and high nozzle pressure ratios. The cavities also yielded a weaker vortex street in the near wake in the vicinity of the nozzle exit, causing a slight increase in the base pressure for low Mach numbers. The wall pressure studies showed that the introduction of cavities generated secondary vortices which reduced the oscillatory nature of the flow along the duct length. The generation of secondary vortices was confirmed by a numerical analysis of the suddenly expanded flow field without and with annular cavities. The two-dimensional coupled implicit Reynolds Averaged Navier-Stokes equations and the two equation standard k-ε turbulence model simulated the process numerically. The governing equations (continuity, momentum, and energy), along with the boundary conditions, were solved by the finite element method. They were flow patterns for various combinations of the process variables demonstrated that there is formation of secondary vortices for flows with annular cavities. Due to the formation of near wake and free shear instability, the vortices of these flows caused the boundary layer to roll up, forming secondary vortices in the suddenly expanded flow field. Immediately following their formation, the vortices underwent a strong three-dimensional distortion.